Effect of additional strengthening of colonic anastomosis on abdominal contamination severity - Mylytsia, M. M.; Mylytsia, К. M.; Steblianko, V. V.; Soldusova, V. V.; Kazakov, V. S. (Modern medical technology, 2021)
Purpose of the study. To investigate the effect of additional strengthening of the colonic anastomosis (CA) using modern adhesive materials on the severity of abdominal contamination in patients with insulin resistance (IR). Materials and methods. The study involved 80 patients with IR, who underwent surgery with the CA imposition (median age of the patients – 64 (57; 71) years). All patients were divided into 2 groups, depending on the method of strengthening the CA suture: 1 group – 40 patients who underwent the application of a onerow continuous suture (OCS) of the CA (median age of patients – 65 (57; 75) years, 2 group – 40 patients to whom OCS CA was applied, and in order to seal and strengthen the anastomosis zone a modern Nbutylcyanoacrylate tissue adhesive was added (median age of patients – 63,5 (58,5; 70,5) years. The spectrum of microbial flora of secretions from drains near the anastomosis was determined. Results. The additional use of modern Nbutylcyanoacrylate tissue adhesive to strengthen the area of CA with the imposition of a OCS in patients with IR contributes to a reliable reduction of number of patients with associations consisting of two types of microorganisms compared to the patients without additional strengthening (2 (5,0%) versus 9 (22,5%) of patients, respectively) (χ2 = 5,17, df = 1; р < 0,05), the greater number of patients with no growth of microorganisms in crops from the anastomotic zone ((11 (27,5%) of patients versus 3 (7, 5%) of patients, respectively), as well as fewer cases of high degree of anastomosis zone contamination (3,48 times (χ2 = 7,68, df = 1; р < 0,05)), with prevalence of mild contamination (3, 35 times (χ2 = 15,24, df = 1; р < 0,05)). Conclusion. The additional use of modern Nbutylcyanoacrylate tissue adhesive to strengthen the area of CA with the imposition of a onerow continuous suture in patients with IR contributes to a reliable reduction of contamination of the area around the anastomosis compared to the patients without additional strengthening.